Bullet Markers - A Simple Technique To Assist In The Evaluation Of Penetrating Trauma. Issue 3 (1st September 2002) - Brooks, A; Bowley, DMG; Boffard, K D
Abstract : Radio-opaque markers in penetrating trauma are useful in both the clinical evaluation of the injuries and in the permanent record of the location of the wounds. The use of an unfolded paperclip taped over the wound as a marker is recommended as a valuable adjunct in the radiological evaluation of penetrating trauma.